2018 IEEE International Conference on Systems, Man, and Cybernetics (SMC) 2018
DOI: 10.1109/smc.2018.00266
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Wearable Wheelchair Monitor: Classification of Push Style Based on Inertial Sensors at Multiple Upper Limb Locations

Abstract: Measuring manual wheelchair activity by using wearable sensors is on the rise for rehabilitation and monitoring purposes. Stroke pattern is an important descriptor of the wheelchair user's quality of movement. This paper evaluates the capability of inertial sensors located at different upper limb locations plus wheel, to classify two types of stroke pattern for manual wheelchairs: semicircle and arc. Data was collected using bespoke inertial sensors with a wheelchair fixed to a treadmill. Classification was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The interaction of stroke pattern on inertia sensor accuracy during MWC propulsion is an emerging field of study, but a recent report showed the greatest accuracy when a forearm sensor was combined with a wheel sensor. 18 Manual wheelchair users will need to provide feedback on the amount of instrumentation that they are willing to wear and the minimum level of accuracy that is acceptable for real-life, home-use, propulsion assistance neuroprostheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of stroke pattern on inertia sensor accuracy during MWC propulsion is an emerging field of study, but a recent report showed the greatest accuracy when a forearm sensor was combined with a wheel sensor. 18 Manual wheelchair users will need to provide feedback on the amount of instrumentation that they are willing to wear and the minimum level of accuracy that is acceptable for real-life, home-use, propulsion assistance neuroprostheses.…”
Section: Discussionmentioning
confidence: 99%
“…Accelerometers or inertial measurement units (IMUs) have been used to identify wheelchair propulsion activities and distinguish whether wheelchair users are propelling themselves or being pushed by an attendant, 15,16 discriminate between the most common push styles, 15,17,18 and separate minimal wheelchair movements from everyday tasks. 19,20 Generally, wheel-mounted…”
mentioning
confidence: 99%